Castor seed oil brings smiles in Côte d'Ivoire - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Castor seed oil is used in medicine as a purgative. It has an unpleasant taste, and those who have to take it usually pull quite a face. In Côte d'Ivoire, though, it is bringing smiles to the faces of its potential growers. The West African association of castor seed growers launched some experimental crops which, the daily paper Fraternité Matin reports, have led to encouraging results from the very beginning. Trials were conducted on four hybrid varieties that came originally from Costa Rica in Central America. They yielded two to eight tonnes of seeds per hectare. Castor seed cultivation is set to become a promising route to follow in diversifying agricultural production. It is easy to grow ? in Côte d'Ivoire, castor seed plants grow naturally on rubbish dumps; and it has a valuable market ? its oil is used in the manufacture of varnish, paints and lubricants in the automobile industry. In the United States alone, 40,000 tonnes are consumed annually. The final conclusions of the trials should be awaited before people start trying to overtake India, world champion in castor seed oil production, but this is clearly a crop to watch.